VITAMIN D DEFICIENCY AS A RISK FACTOR OF RECALCITRANT RECURRENT INTRAORAL HERPES (RIH) - Iin Heldayani; Wahyu Hidayat (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: Recurrent Intraoral Herpes (RIH) is secondary infection due to Herpes Simplex Virus (HSV) which is latent and most often involves lips and oral cavity. RIH infection could be reactivated as triggered by various factors, such as stress, immunosuppressant, hormonal, sunlight exposure or vitamin D deficiency. Objective: To describe vitamin D deficiency as a risk factor of recalcitrant RIH. Case: A 22-year-old woman came to Oral Medicine Clinic of RSUP. Dr. Hasan Sadikin Bandung with complaints of recurrent stomatitis for two years. Her stomatitis was recalcitrant and recurred several times a month. Intraoral examination revealed ulcers with yellowish-white base surrounded by haloerytem on the right of buccal and tongue lateral and oropharynx. Immunoserology laboratory examination showed an increasement of IgG HSV-1 value and vitamin D (25-OH) deficiency. Case Management: Patient was given Acyclovir 200mg 5 times daily for a week and Hyaluronic Acid 0.025% mouthwash as well as education to maintain an oral hygiene. Lesions were healed after 10 days therapy. However, 3 days later, lesion on the right buccal recurred with bigger size. Therapy was continued with additional administration of vitamin D and instructions to increase consumption of fruits, vegetables and to bask in the sun. Lesions of recalcitrant RIH were completely healed on the 5th visit or 45 days’ therapy. Conclusion: Vitamin D plays a role in all of the body's defense mechanisms and could be given to reduce the high recurrence rate of RIH as vitamin D has a protective effect against viral infections, particularly against HSV. Keywords: Deficiency Vitamin D, Herpes Infection, Recalcitrant, Recurrent Intraoral Herpes.